Fatty acid composition and distribution in triacylglycerols of cultured fishes in Japan. (January 2021) - Mochizuki, Mamiko; Matsuyama, Hajime; Suzuki, Kunihiro; Watanabe, Yomi
Abstract: Lipids were extracted from marine and fresh-water fishes aqua-cultured in Japan in 2019. Lipid contents of culture diets were 6.1–7.0% with similar fatty acid (FA) compositions and FA distributions. The lipid contents in the fleshes of aqua-cultured marine fishes, namely, striped jack, red seabream, Japanese horse mackerel, were 1.8–2.6%, and that of the rainbow trout was 5.2%. The major FAs over 5 mol% were 16:0, 16:1, 18:1, 18:2, and DHA. All cultured fishes were rich in DHA, 7.2–11.9%. Intake of less than 100 g portion/d of cultured trout would satisfy the supplementation of 0.5 g EPA+DHA/d, which the daily intake for healthy adults to maintain healthy cardiovascular system recommended by International Society for the Study of Fatty Acids and Lipids. Though the differences in FA compositions between fish species, or between the flesh portions of rainbow trout were not distinct, FA distributions in triacylglycerols differed by each FA and fish species; 14:0 and 16:0 was distributed mainly at the sn -2 position in striped jack and red sea bream, evenly distributed in Japanese horse mackerel, and little at sn -2 in rainbow trout. The opposite distribution pattern was shown for 18:1. In all fishes, 18:0 was mainly distributed at sn -1(3) and DHA at sn -2. Highlights: Lipid contents of marine and fresh-water fishes cultured in Shizuoka, Japan in 2019, were 2-5%, those in the diets were 7%. FA distributions in triacylglycerols, differed by each FA and fish species, though the total FA compositions were similar. 14:0 and 16:0 were distributed mainly at  sn -2 position in striped jack and red sea bream. 14:0 and 16:0 were evenly distributed in Japanese horse mackerel, and little at sn -2 in rainbow trout. In all fishes, 18:0 was mainly distributed at sn -1(3) and DHA at sn -2. Intake of <100 g trout/d would satisfy 0.5 g EPA+DHA/d supplementation to contribute to keep healthy cardiovascular system.